2009
DOI: 10.1016/j.colsurfa.2008.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of atrazine onto humic acids (HAs) coated nanoparticles

Abstract: a b s t r a c tWith the development of nanotechnologies, a large number of nano-materials with novel properties are being released into the environment. However, little is known about their fate, transport, toxicity and interactions with organic matters in aqueous environment. In this study, nano-SiO 2 or kaolinite, coated with soil humic acid (SHA) and peat humic acid (PHA), were used as sorbents. The original and HA-coated nanoparticles were characterized for particle size, TEM and electrophoretic mobility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The decrement became more substantial under a higher atrazine loading. In fact, the similar phenomenon was also reported by Lu et al (2009), who observed the amount of sorbed atrazine on humic acid-coated nanoparticles was significantly lower than that on the original ones. This can be partially ascribed to the increase in the hydrophility of the SDBC surface by humic acids.…”
Section: Influence Of Humic Acids On Atrazine Immobilizationsupporting
confidence: 80%
“…The decrement became more substantial under a higher atrazine loading. In fact, the similar phenomenon was also reported by Lu et al (2009), who observed the amount of sorbed atrazine on humic acid-coated nanoparticles was significantly lower than that on the original ones. This can be partially ascribed to the increase in the hydrophility of the SDBC surface by humic acids.…”
Section: Influence Of Humic Acids On Atrazine Immobilizationsupporting
confidence: 80%
“…Lu et al 29 reported that sorption of atrazine on HA-coated mineral nanoparticles was apparently lower than that on original particles. They found that the surface area of HA-coated nanoparticles was reduced due to the pore-blockage effect.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…All these fields are unified by one goal, which is the development of new materials with certain properties. To achieve this goal, a number of researchers investigate the interaction of HS with different colloids and nanoparticles [3][4][5][6]. In this aspect, carbon-based nanomaterianls should be taken into critical account.…”
Section: Introductionmentioning
confidence: 99%